The burnout : [large type] a novel - Kinsella, Sophie (Thorndike Press large print top shelf., 2023)
"Sasha has had it. She cannot bring herself to respond to another inane email or participate in the corporate employee joyfulness program. She hasn't seen her friends in months. Sex seems like a lot of effort. Even cooking dinner takes far too much planning. Armed with good intentions, she heads to the seaside resort she loved as a child. But it's the off season, the hotel is in shambles, and she has to share the beach with a grumpy guy named Finn. When curious messages begin to appear, the two are forced to talk--about everything. How did they get so burned out? Can either of them remember something they used to love? And what does the energy between them signify?"--